Medial Turn in Education: Philosophy of Understanding Words and Images - Grigoryev, Sergey L.; Saenko, Natalya R.; Volkova, Polina S.; Kortunov, Vadim V. (Frontiers in Education, 2022)
The research presented in the article aimed to diagnose the profound changes that have taken place in education as a result of the expansion of screen technologies and the introduction of distance interaction in pedagogy. The live-sounding speech of a teacher is the true historical form of paideia as such and the technique of maieutics in particular. Any intermediary, even a writing process, let alone the screen, reduces the effect of pedagogical dialog and produces significant and radical changes in the understanding of meaning. The article deals with the problems of understanding in the pressing context of two turns of educational philosophy: linguistic and medial. The empirical background of these turns is represented, on the one hand, by the increasing extent of the visualized (“printed,” “screened”) word in educational procedures vs. the sounding word, and by the irreversible introduction of screen technologies, digitalization, and distance learning, on the other hand. The consideration is made through the prism of the comprehension-based approach focusing on the values and meanings of professional-pedagogical activity, namely, the systemic approach, the principles of language sign ambivalence, the method of stylistic decoding, the method of analysis of vocabulary definitions, and intertextuality.